Diversivikasi Kayu Secang dalam Meningkatkan Kualitas Produk Makanan Tradisional - Rachma Indrarini; Lucky Rachmawati; Mauren Gita; Shinta Lintang; Andi Fahrudin (Inspirasi Nusantara, 2021)
Modern lifestyle requires every human being to be able to move quickly both inside and outside the room. Various kinds of health risks can threaten all human activities, one of which is the free radical element. Many things can be done to prevent free radicals, namely healthy living, by exercising and consuming food and drinks that are beneficial to our body. Wedang secang is one drink that is beneficial to the body, made from wood extract of secang and other herbs. Our partner Ms. Windi is a secang drink maker. Mrs. Windi packs a drink with a bottle. However, the beverage can not last long, in two days the beverage has been fermented. Based on that, the Community Service was conducted to provide diversification of secang drinks into secang candy and secang powder using FGD and workshops. Not only making products, but also taught packaging and marketing procedures.